A novel closed chest drainage device - Huang, Shaoqing; Song, Xu; Shi, Qiang; Li, Jie (Frontiers in Medicine, 2025)
PurposeNegative pressure closed thoracic drainage improves drainage efficiency, accelerates the removal of fluid and air, and facilitates lung re-expansion. Conventional wall negative pressure systems restrict patient mobility, while digital drainage devices are associated with high costs that hinder widespread clinical adoption. Hence, there is an urgent need for a cost-effective, practical, and portable negative pressure drainage system.MethodsBased on the principles outlined in the Chinese national patent (ZL 202122505281.4), we innovatively integrated a micro-pump and power system into a compact, portable negative pressure generator, which was then connected to the pressure-regulating chamber of a conventional three-chamber closed drainage bottle. This integration resulted in a novel portable closed thoracic drainage device with active negative pressure control. The device underwent in vitro testing followed by preliminary proof-of-concept evaluation.ResultsThe test results indicate that the novel closed thoracic drainage device can achieve a maximum negative pressure of approximately 20 cm H₂O and a maximum airflow rate of 15 L/min. The novel device was initially used in three patients.ConclusionA novel type of negative pressure closed thoracic drainage device has been successfully developed and a preliminary concept verification has been carried out. This device offers the advantages of cost-effectiveness and portability, demonstrating potential for wide application in postoperative thoracic drainage following lung surgery.